Local Tourism, Social Innovations (ENTRENOVA - ENTerprise REsearch InNOVAtion Journal, 2018)
Several studies and researches investigate the innovation ability of tourism. The research topic is also interesting, because even the European Union subsidises innovation development and tourism, as a major branch of the service sector, is responsible for the vast majority of the domestic GPPs. Linking these two is an important field of research for a practical perspective as well. The development of technology and ICT harbinger the further advance of tourism. At the same time the question, how such an important branch takes its share of the development of socially important factors, i.e. what answer can touristic stakeholders give to managing current social challenges, can also be raised. Some results of a research conducted in the past year will be presented in the followings. The research question was what social innovation potentials local tourism organizations have, i.e. how their continuous renewal activities help the management of socially important challenges. Factors hindering the innovation of these groups were also researched, along with future innovation plans.This work is licensed under a Creative Commons Attribution-NonCommercial 4.0 International License.